2018
DOI: 10.1002/2017gl076884
|View full text |Cite
|
Sign up to set email alerts
|

Increased Winter‐Mean Wave Height, Variability, and Periodicity in the Northeast Atlantic Over 1949–2017

Abstract: A 69‐year (1948–2017) numerical weather and wave hindcast is used to investigate the interannual variability and trend of winter wave height along the west coast of Europe. Results show that the winter‐mean wave height, variability, and periodicity all increased significantly in the northeast Atlantic over the last seven decades which primarily correlate with changes in the climate indices North Atlantic Oscillation (NAO) and West Europe Pressure Anomaly (WEPA) affecting atmospheric circulation in the North At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
90
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 63 publications
12
90
0
1
Order By: Relevance
“…Valiente et al (2019) show that sheetflow conditions may occur around 30-40-m depth under extreme storm conditions. The region has been subject to a significant increase in extreme (99th percentile) H s of 1% per annum, among the largest increases observed globally, and an increase in winter H s and interannual variability associated with the North Atlantic Oscillation and West European Pressure Anomaly indexes (Castelle et al, 2017(Castelle et al, , 2018Young et al, 2011). Positive West European Pressure Anomaly values result in higher wave heights south of 52°N and increased storm clustering (Castelle et al, 2017;Hanley & Caballero, 2012;Scott et al, 2016).…”
Section: Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…Valiente et al (2019) show that sheetflow conditions may occur around 30-40-m depth under extreme storm conditions. The region has been subject to a significant increase in extreme (99th percentile) H s of 1% per annum, among the largest increases observed globally, and an increase in winter H s and interannual variability associated with the North Atlantic Oscillation and West European Pressure Anomaly indexes (Castelle et al, 2017(Castelle et al, , 2018Young et al, 2011). Positive West European Pressure Anomaly values result in higher wave heights south of 52°N and increased storm clustering (Castelle et al, 2017;Hanley & Caballero, 2012;Scott et al, 2016).…”
Section: Wavesmentioning
confidence: 99%
“…The relative incident wave angle to the steady flow influences the vertical current profile and variation in apparent bed roughness, demonstrated by analytical and numerical models (Fredsøe, ; Grant & Madsen, , ; Olabarrieta et al, ; Tambroni et al, ). With significant positive trends observed in global 99th percentile wave heights from 1991 to 2008 in buoy and altimeter data (Young et al, ), and upward trends in storminess across central, western, and northern Europe (Castelle et al, ; Donal et al, ), understanding the effect of waves on shelf sediment transport is potentially of increasing importance to coastal communities.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the 2013–14 winter was associated with the highest WEPA over 1948–2016, which reflects an intensified and southward shift of the sea‐level pressure difference between the Icelandic low and the Azores high, driving severe storms that funnel high‐energy waves toward western Europe southward of 52° N. This high WEPA was linked to a recent increase in inter‐annual variability, which was also observed in the winter‐wave variability along western Europe (Castelle et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Interactions with stakeholders (such as fisheries and coastal planners) have highlighted the importance of understanding future changes in waves under high‐end climate change. Castelle et al () show that winter wave height around Europe has increased significantly since 1984, as well as variability in wave conditions. Large/long‐period waves are the most damaging for overtopping (Palmer et al, ).…”
Section: Introductionmentioning
confidence: 99%